Waiting for you - Colasanti, Susane (New York : Viking, 2009)
Fifteen-year-old high school sophomore Marisa, who has an anxiety disorder, decides that this is the year she will get what she wants--a boyfriend and a social life--but things do not turn out exactly the way she expects them to.
Keywords: Interpersonal relations -- Fiction; Dating (Social customs) -- Fiction; Anxiety disorders -- Fiction; High schools -- Fiction; Schools -- Fiction; Families -- Fiction; Divorce -- Fiction